Multidisciplinary management of acute type A aortic dissection presenting with atypical symptoms, abdominal hemorrhage, and Rh-negative blood type: a case report - Yuning Xi; Meng Yu; Yuhang Lv; Liang Dong (Frontiers in Cardiovascular Medicine, 2026)
Background Acute type A aortic dissection (TAAD) is a catastrophic cardiovascular emergency with high mortality. Patients presenting with atypical gastrointestinal symptoms, such as abdominal pain and diarrhea, are particularly prone to misdiagnosis. Visceral branch vessel injury caused by the dissection can directly lead to abdominal hemorrhage, a rare but fatal complication. Case summary We report a case of a 66-year-old man who presented with a one-day history of abdominal pain and diarrhea, followed by chest tightness and shortness of breath for 10 hours. Computed tomography angiography (CTA) revealed a DeBakey type I TAAD involving the celiac trunk and superior mesenteric artery, with suspected active abdominal hemorrhage. The patient had a rare Rh-negative B blood type. Emergency “Sun's procedure” was performed. Postoperatively, the pre-existing abdominal hemorrhage was exacerbated by coagulopathy and surgical stress, leading to hemorrhagic shock. Following multidisciplinary discussion, given the diffuse nature of the bleeding, a stepwise hemostatic strategy of “interventional embolization first, surgical exploration as backup” was adopted. The patient subsequently developed liver dysfunction and diarrhea, which may be attributed to visceral ischemia-reperfusion injury. He ultimately recovered after comprehensive management. Conclusion Unexplained shock with acute abdominal pain, especially in hypertensive patients, should raise suspicion for TAAD and prompt early aortic CTA. TAAD-related abdominal hemorrhage may be recognized as a manifestation of systemic vascular injury. Management may benefit from an understanding of the multi-factor cascading pathophysiological model and could follow a stepwise hemostatic approach. In the context of massive hemorrhage with a rare blood type, a rapid blood supply system is essential. Meticulous perioperative monitoring and efficient multidisciplinary collaboration are cornerstones of successful resuscitation in such complex cases.